Bombay blood group discovered incidentally in a middle-aged female posted for hemithyroidectomy: A near miss - Archana Shetty; Bhargavi K. N; Supriya T. R; Aishwarya Muralidharan (Journal of Krishna Institute of Medical Sciences University, 2024)
ABO is the most widely utilized blood group system. Bombay blood group is a rare subtype of autosomal recessive group with absence of H antigen and presence of anti-H, anti-Aand anti-B antibodies. We present a case of a 51-yearold lady posted for hemithyroidectomy and incidentally detected to be of Bombay blood group when a blood unit was reserved for surgery. She was a non-secretor for H substance on saliva inhibition test. History of consanguineous marriage was present. We wish to reaffirm that ardent effort has to be undertaken to confirm all 'O' group individuals with reverse grouping during routine testing for blood groups, failing which the rare Bombay blood group can be misdiagnosed as 'O' resulting in an acute haemolytic reaction if any unit other than that of Bombay blood group is transfused. Individuals with this group need to be counselled about rarity and clinical implications of the same.